Evaluation of syndromic approach of vaginal discharge flowchart to diagnosis of trichomoniasis - Glehn, Mateus de Paula Von; Machado, Eleuza Rodrigues (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: Trichomonas vaginalis infection is the most prevalent non-viral sexually transmitted disease in the world. Among the different methods for diagnosis, the World Health Organization and Ministry of Health of Brazil proposes the use of flowcharts in the syndromic approach. Objective: To evaluate the syndromic approach of vaginal discharge to diagnosis of T. vaginalis infection. Methods: Transversal study with sample of outpatient population consisting of women in reproductive age. After exclusion of pregnant women and minor girls, the final sample consisted of women between 18 and 49 years old. The participants answered a questionnaire where the complaints were registered. They were examined, had the vaginal pH assessed and sample tested with 10% KOH solution to verify the exhalation of amine odor (whiff test). After this proceeding, a vaginal secretion sample was inoculated in a specific T. vaginalis culture medium. The culture results were used as the gold standard to evaluate the syndromic approach flowchart. The algorithm was evaluated according sensitivity, specificity, accuracy, and predictive values. Results: Among women with T. vaginalis infection, 10% were asymptomatic; among them, dyspareunia was significantly higher, if compared to women with no infection. Flowchart proposed by the syndromic approach had low specificity and accuracy, leading to unnecessary treatment in two-third of women. Conclusion: The diagnosis of trichomoniasis based only on the discharge complaint had low accuracy; the whiff test result improves the specificity of diagnosis of T. vaginalis infection, regardless of the vaginal pH value.